2020
DOI: 10.5551/jat.49791
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Circulating Inflammatory Monocytes and Cardiovascular Disease Measures of Carotid Intimal Thickness

Abstract: The official journal of the Japan Atherosclerosis Society and the Asian Pacific Society of Atherosclerosis and Vascular Diseases Original Article Aims: Cardiovascular disease (CVD) remains the leading cause of death worldwide despite improvements in the treatment of atherosclerosis, an inflammatory disease and major underlying cause of CVD. Monocytes, an innate immune cell type, are linked to CVD progression; however, given their heterogeneity, the association between distinct monocyte subsets and increased ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…Based on these markers, 5 of the 8 classical monocyte subsets were called ( Figure 2C ) and related to subsets described by mass cytometry. 78 Intermediate CD14+CD16+ monocytes (INT) have been considered pro-inflammatory by several investigators 7983 and are known to be increased in people with HIV 84, 85 and with CVD. 82, 86, 87 All intermediate monocytes highly expressed the inflammation-induced costimulatory molecule CD86 ( Figure 2C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these markers, 5 of the 8 classical monocyte subsets were called ( Figure 2C ) and related to subsets described by mass cytometry. 78 Intermediate CD14+CD16+ monocytes (INT) have been considered pro-inflammatory by several investigators 7983 and are known to be increased in people with HIV 84, 85 and with CVD. 82, 86, 87 All intermediate monocytes highly expressed the inflammation-induced costimulatory molecule CD86 ( Figure 2C ).…”
Section: Resultsmentioning
confidence: 99%
“…Tissue factor expression on monocytes has previously been shown to be increased in HIV+ subjects. [45] Intermediate monocytes are considered pro-atherogenic, [44] and tissue factor expression provides a plausible reason for this. We found that in INT2 and INT3, the inflammatory chemokines CCL3 and In CD4T cells clusters 1, 2 and 8, IL-32 was highly significantly increased by CVD, which was reversed by cholesterol lowering in CD4T1 and 2 (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Many factors, including increased production of proinflammatory cytokines, oxidative stress, acidosis, altered lipid metabolism, accumulation of uremic toxins such as indoxyl sulfate, and gut microbiota dysbiosis, contribute to the setting of inflammatory status of CKD. Relationship between circulating inflammatory monocytes and carotid IMT has also been recently reported 7) . Thus, inflammatory status of CKD might promote the accelerated increase of carotid IMT.…”
mentioning
confidence: 85%
“…Conversely, limited prospective studies have reported conflicting relation of differential leukocyte counts with CVD incidence. Several studies demonstrated that higher neutrophil count increased the risk of CVD incidence [27][28][29] , and monocyte count was also reported as a risk factor for CVD, CHD, and IS 15,30,31) . However, eosinophil and lymphocyte counts were reported to be inversely associated with the risk of CVD 32) .…”
Section: Measurement Of Leukocyte Countsmentioning
confidence: 99%